The Effect of Competitive Advantage, Internationalization on Profitability with R&D Intensity and Marketing Intensity as Antecedents: Evidence from Indonesian Manufacturing Companies - Mustafa, Muthyah Ainunsary; Nuzula, Nila Firdausi; Worokinasih, Saparila (Universitas Negeri Malang, 2025)
Companies are required to always have a strategy that can increase profitability and strengthen their competitive advantage. One of the factors that can affect a company's profitability is competitive advantage (CA) and Internationalization. In order to have CA and internationalization, the company can manage and utilize its various capabilities through research and development (R&D) and marketing methods owned by the company. This relationship is explained in the RBT and internalization theory. This study aims to analyze and explain the influence of CA and internationalization on profitability with R&D Intensity and marketing intensity as antecedents. This study uses a purposive sampling technique with several criteria so that a sample of 15 manufacturing companies listed on the IDX for the 2018-2022 period was obtained. The results of this study indicate that R&D Intensity and Marketing Intensity have a significant effect on CA, R&D intensity has no significant effect on Internationalization, Marketing Intensity and CA have a significant effect on internationalization, CA has a significant effect on Profitability, Internationalization has no significant effect on Profitability, CA can mediate the effect of R&D intensity and marketing intensity on profitability, and internationalization is not able to mediate the effect of R&D intensity and marketing intensity on profitability. Keywords: Competitive Advantage, Profitability, R&D Intensity, Marketing Intensity